2012
DOI: 10.1111/j.1365-2753.2012.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous education for evidence‐based medicine practice on knowledge, attitudes and skills of medical students

Abstract: Continuous EBM education through small-group discussion and learner-centred, problem-based self-practice can be a useful way to improve a medical student's knowledge, attitudes and skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 24 publications
2
27
0
3
Order By: Relevance
“…This result might indicate that the EBM course had achieved its goals at least in some aspects. Earlier studies also reported the impact of the EBM program on students’ knowledge (810, 14), skills (6, 914), and attitudes toward learning and applying EBM (10, 11, 13, 14). As with the medical students participating in our study, researchers have also approved that implementing EBM programs during the clinical clerkships may support students in practicing these skills (6, 16).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This result might indicate that the EBM course had achieved its goals at least in some aspects. Earlier studies also reported the impact of the EBM program on students’ knowledge (810, 14), skills (6, 914), and attitudes toward learning and applying EBM (10, 11, 13, 14). As with the medical students participating in our study, researchers have also approved that implementing EBM programs during the clinical clerkships may support students in practicing these skills (6, 16).…”
Section: Discussionmentioning
confidence: 93%
“…In response to this recommendation, the teaching of EBM has become widespread in medical education at the undergraduate and graduate levels (6) with a variety of methods and content (7). Studies have aimed to evaluate the impact of EBM programs on the students’ knowledge level (8–11), performance in searching skills (12, 13), EBM skills (6, 9–11, 13, 14), attitudes toward learning and applying EBM (10, 11, 13, 14), and self-efficacy in using EBM (15). …”
mentioning
confidence: 99%
“…EBM integration has been shown to improve students' attitudes toward EBM, 18 increase students' satisfaction with EBM training, 19 and raise students' level of EBM knowledge, 20 suggesting that this is a warranted approach for teaching EBM. Additionally, the integration of EBM into other courses and content may help decompress the curricular time needed to teach EBM, which has been identified as a barrier to teaching EBM.…”
Section: Discussionmentioning
confidence: 98%
“…Wanvarie et al similarly integrating EBM longitudinally throughout the medical curriculum with students showing they were capable of completing the five steps by reporting high grades on EBM individual assignments and self evaluation [10]. Liabsuetrakul et al illustrated that the integration of EBM using small group discussion with case scenarios and problem-based learning enhanced their knowledge and skills of EBM in medical students [11].…”
Section: Teaching Evidence Based Medicinementioning
confidence: 99%